Organized hematoma of the sphenoid sinus causing acute visual loss. Issue 6 (November 2018) - Yoon, Young Hoon; Kim, Sung Ha; Kim, Yong Min; Rha, Ki-Sang
Sinonasal organized hematoma, which has locally aggressive characteristics, is a non-neoplastic disease. We report a rare case of sphenoid sinus organized hematoma causing acute visual loss. A 35-year-old male presented with progressive headaches, retro-orbital pain, and frequent epistaxis. He had a medical history of aplastic anemia and of taking warfarin for a valvular heart disease. On image studies, an expansive soft tissue density lesion with bony destruction was found in his left sphenoid sinus. While waiting for elective surgery, acute visual loss occurred. Emergent endoscopic surgery was performed after correction of abnormal hematological profiles, but his visual disturbance did not improve. Although sphenoid sinus organized hematoma is a rare disease, organized hematoma should be considered in the differential diagnosis for sphenoid sinus lesion with acute visual loss. Rapid and correct diagnosis and timely treatment are essential to prevent permanent sequela.